Special Symposium on "Financial instability and crisis" - Philip Arestis; Robert A. Blecker; Marica Frangakis; Marc Lavoie (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: In early August 2009 the 2nd Summer School of the Research Network Macroeconomics and Macroeconomic Policies (FMM) was held in Berlin. As in the previous year, about 50 graduate students, young researchers and senior lecturers from all over the world came together to discuss »Keynesian Macroeconomics and European Economic Policies«. In response to current macroeconomic events, a panel discussion was organised, in which the global economic crisis and the prospects for alternative macroeconomic theories were debated. The participants in the panel debate were asked to provide written answers to some of the questions discussed in Berlin. These answers are documented below. The questions were asked by Till van Treeck from the Macroeconomic Policy Institute (IMK) in the Hans Boeckler Foundation in Duesseldorf.
Keywords: 330